Pengaruh Harga, Promosi Dan Rating Terhadap Keputusan Pembelian Di Marketplace Shopee - Yana Kumara Kristanti; Rayhan Gunaningrat (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
This research aims to determine the influence of price, promotion and rating on purchasing decisions in the Shopee marketplace. The approach used in this research is a quantitative approach with an explanatory research type. The sampling technique in this research was a purposive sampling technique with the sample used amounting to 100 respondents. The data collection technique uses online questionnaire distribution with the help of Google forms. Data analysis techniques in this research are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test, coefficient of determination test, f test and t test. Based on the data research analysis, the results showed that there was an influence of price on purchasing decisions, there was an influence of promotion on purchasing decisions, there was no influence of ratings on purchasing decisions and the f test showed that there was a simultaneous influence of price, promotion and rating on purchasing decisions. The results of the coefficient of determination test show an r square value of 0.472, which means that the influence of the price (x1), promotion (x2) and rating (x3) variables simultaneously on the purchasing decision variable (y) is 47.2%.